2020
DOI: 10.1002/ccd.29377
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of rotational and excimer lASER coronary atherectomy (RASER) during complex coronary angioplasty—An analysis of cases (2006–2016) from the British Cardiovascular Intervention Society database

Abstract: Introduction Combining rotational (RA) and excimer laser coronary atherectomy (ELCA)—RASER atherectomy—is technique utilized in the percutaneous management of calcific coronary disease. The evidence base examining its safety and utility is sparse and limited to small case‐series. This study examines the patterns and outcomes of RASER atherectomy use in the largest cohort to date. Methods Using the British Cardiac Intervention Society database, data were analyzed on all PCI procedures in the UK between 2006 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Danek et al [ 22 ], in a study based on data from the PROGRESS-CTO registry, the rate of coronary perforation was much higher when ELCA was used than when it was not (7% vs. 2%, respectively; p < 0.009). Protty et al [ 23 ] also reported that ELCA was associated with a higher coronary perforation rate (odds ratio: 2.18, 95% confidence interval: 1.44–3.30) based on data from the British Cardiovascular Intervention Society database. For ISR CTO procedures, the wires may not remain in the true lumen as they are advanced in some segments; therefore, ELCA requires experienced operators, and operators must be cautious to avoid this kind of serious complication.…”
Section: Discussionmentioning
confidence: 99%
“…Danek et al [ 22 ], in a study based on data from the PROGRESS-CTO registry, the rate of coronary perforation was much higher when ELCA was used than when it was not (7% vs. 2%, respectively; p < 0.009). Protty et al [ 23 ] also reported that ELCA was associated with a higher coronary perforation rate (odds ratio: 2.18, 95% confidence interval: 1.44–3.30) based on data from the British Cardiovascular Intervention Society database. For ISR CTO procedures, the wires may not remain in the true lumen as they are advanced in some segments; therefore, ELCA requires experienced operators, and operators must be cautious to avoid this kind of serious complication.…”
Section: Discussionmentioning
confidence: 99%
“…Further applications of ELCA include a combination technique that utilizes both RA and ELCA simultaneously for modification of heavily calcified lesions. This technique, termed RASER atherectomy, was introduced in 2012 24 and was recently examined in a large retrospective study using data from the British Cardiac Intervention Society database between 2006 and 2016 25 . Outcomes of the RASER technique were significant for a higher incidence of arterial complications (OR: 3.23, 95% CI: 1.58–6.61), slow flow (OR: 3.50, 95% CI: 1.29–9.55), and shock (OR: 9.66, 95% CI: 3.44–27.06), without an increase in the likelihood of major bleeding, major adverse cardiovascular and cerebrovascular events, or death 25 …”
Section: Indicationsmentioning
confidence: 99%
“…25 Outcomes of the RASER technique were significant for a higher incidence of arterial complications (OR: 3.23, 95% CI: 1.58-6.61), slow flow (OR: 3.50, 95% CI: 1.29-9.55), and shock (OR: 9.66, 95% CI: 3.44-27.06), without an increase in the likelihood of major bleeding, major adverse cardiovascular and cerebrovascular events, or death. 25…”
Section: Ctos And/or Uncrossable Lesionsmentioning
confidence: 99%
“…Although RA can be performed in the presence of severe calcification, it is contraindicated in AMI, while ELCA is highly useful in acute settings. Recently, ELCA combined with RA in severely calcified lesions has been described as “RASER” [ 132 , 133 ]. The clinical effect of excimer laser combined with traditional PCI, RA, and DCB is better than that of a single method.…”
Section: Research Progress and Applications Of Laser Technology In Intravascular Imaging And Treatmentmentioning
confidence: 99%